Hacker proof - Jamsa, Kris (Thomson, 2002)
Hacker Proof: The Ultimate Guide to Network Security provides a detailed examination of the security concepts network administrators, programmers, and Webmasters must know. The first edition was the original Hacker book and now the updated second edition is even better! Nonprogrammers will readily understand security threats and the steps they must perform to prevent them. Programmers will be thrilled with the detailed programming examples that demonstrate how hackers penetrate the most secure computer systems, The book's companion CD-ROM includes software users can run to test their system's security and look at hacker scenarios